2020
DOI: 10.3390/ijms21238919
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory RNAs: A Universal Language for Inter-Domain Communication

Abstract: In eukaryotes, microRNAs (miRNAs) have roles in development, homeostasis, disease and the immune response. Recent work has shown that plant and mammalian miRNAs also mediate cross-kingdom and cross-domain communications. However, these studies remain controversial and are lacking critical mechanistic explanations. Bacteria do not produce miRNAs themselves, and therefore it is unclear how these eukaryotic RNA molecules could function in the bacterial recipient. In this review, we compare and contrast the biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 138 publications
(189 reference statements)
0
23
0
Order By: Relevance
“…White et al (2020) compared small RNAs in ELVs from T. muris and Heligmosomoides bakeri and found they were quite distinct from each other and concluded that this did not depend on their method of preparation but reflected their different intestinal niches and different functions within their hosts. Layton et al (2020) reviewed regulatory RNAs: miRNAs, siRNAs and piRNAs and advocated that miRNAs played a wider role than mere regulation of transcription of the host but also were involved in communication between different taxonomic kingdoms including microbiota.…”
Section: Exosomes and Exosome-like Vesiclesmentioning
confidence: 99%
“…White et al (2020) compared small RNAs in ELVs from T. muris and Heligmosomoides bakeri and found they were quite distinct from each other and concluded that this did not depend on their method of preparation but reflected their different intestinal niches and different functions within their hosts. Layton et al (2020) reviewed regulatory RNAs: miRNAs, siRNAs and piRNAs and advocated that miRNAs played a wider role than mere regulation of transcription of the host but also were involved in communication between different taxonomic kingdoms including microbiota.…”
Section: Exosomes and Exosome-like Vesiclesmentioning
confidence: 99%
“…All of the remaining RNAs belong to a vast group of noncoding RNAs (ncRNAs). Based on their functions, ncRNAs can be classified as housekeeping RNAs or regulatory RNAs [ 3 , 4 ]. Housekeeping ncRNAs, including transfer RNAs (tRNAs), small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs) and ribosomal RNAs (rRNAs), are commonly expressed constitutively.…”
Section: General Remarksmentioning
confidence: 99%
“…Since the discovery of RNAi in iconic models such as Petunia hybrida , Neurospora crassa , and Caenorhabditis elegans and the discovery of its role in the genome defense against viruses and transposons, the RNAi world has grown with numerous branches showing different pathways involved in the endogenous regulation [ 24 , 28 , 29 , 30 ]. A wide variety of endogenous small RNAs (esRNAs) has been described across the Eukarya domain, showing distinct functional roles in the regulation of gene expression [ 24 , 31 ]. There is a canonical common machinery core in the biogenesis of most of these regulatory esRNAs.…”
Section: Discovery Of the Non-canonical Rna Interference Pathway (Ncrip)mentioning
confidence: 99%